Development and Evaluation of a Cost-Effective UV-Protective Cream Containing Para-Aminobenzoic Acid and Aloe Vera for Indian Climatic Conditions. - Maya Sharma; Ranu Sharma; Hemlata Salvi; P.K. Choudhury (Recent Trends in Cosmetics, 2025)
The increasing incidence of ultraviolet (UV) radiation-induced skin disorders has heightened the demand for effective, affordable photoprotective agents, especially in countries with high sun exposure such as India. This study aimed to develop a cost-effective and efficient UV-B protective cream formulation suitable for populations in Indian latitudes. Para-aminobenzoic acid (PABA) was selected as the primary sunscreening agent due to its high UV-B absorption efficiency, low toxicity, and affordability compared with many synthetic and imported commercial sunscreens. The study was conducted in two main phases: (i) formulation and optimization of cream bases (C1–C6) and (ii) evaluation of the developed formulations for sensory, physicochemical, and photoprotective properties. Base optimization identified formulation C3 as the most suitable candidate for UV-B protection. Six creams containing varying concentrations of PABA (1–3%) and aloe vera (0 or 10%) were prepared using the phase inversion method. All formulations were evaluated for pH, emulsion type, acid and saponification values, extrudibility, spreadability, viscosity, and drug content. Both in-vitro and in-vivo sun protection factor (SPF) values were determined, alongside stability assessments using freeze–thaw cycles. Results indicated that all creams complied with pharmacopeial standards, and SPF values increased proportionally with PABA concentration and aloe vera content. The formulation containing 2% PABA and 10% aloe vera (C5) demonstrated optimal balance between sensory qualities, SPF efficacy (in-vitro SPF: 6.7; in-vivo SPF: 6.2), and stability. The study highlights the potential of cost-effective sunscreen formulations tailored to Indian climatic conditions, providing a practical solution for large-scale public use in low- and middle-income populations.
Keywords: Aloe vera; SPF evaluation; UV-shielding; para-aminobenzoic acid; photoprotection; topical formulation